Studi Deskriptif Kejadian Demam Berdarah Dengue (DBD) Dengan Pendekatan Spasial Di Kota Kupang (Analisis Data sekunder Tahun 2010-2011) - Maran, Albertus Ata; Nurjazuli, Nurjazuli; Suhartono, Suhartono (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2012)
Background :Dengue Haemorrhagic Fever (DHF), an endemic disease in Kupang, has been an enormous healthissue throughout years, as it frequently causes outbreak. The risk factors of the disease, according to certainvariables; time, location, civil and population density, climate, precipitation, temperature, humidity, and diseaseincidence, are still remaining unknown. Therefore, no predictive agent to estimate the DHF outbreak in Kupang hasbeen found.Methode : The research is a obsevasional study, with a spatial approach. The research variables were inspectedat same time and the samples were taken from the whole population; all secondary data on Health Departmentregistration record of Kupang. The data was presented on tables and were analyzed by descriptive method.Result : The result of the secondary data analysis indicated that the endemic trend of DHF profile in Kupang hasbeen decreasing over the last 2 years, however the number of exposed area towards DHF endemic increases. DHFIR showed decreasing trend; particular decline was noted on 2011 (55.45 per 100.000 people) compared to 2010.Highest proportion of DHF patient was found on age 5 – 9 years, followed by age 1 – 4 years, and age 15-19 years.There was changed phenomenon in time, distribution pattern and age; from younger age into productive age,with increasing proportion. There were 6 kecamatan and 44 kelurahan that proned to DHF. DHF IR reached thehighest point at 2010, in Kecamatan Kota Raja (122.80 per 100.000 people), the lowest point indicated atKecamatan Kelapa Lima 50.55 per 100.000 people. In 2011, highest IR was indicated at Kecamatan Kota Lama(84.64 per 100.000 people) while the lowest IR indicated at Kecamatan Alak (35.40 per 100.000 people). Certainfactors are believed to take effect on DHF incidence, these factors are; population density, location, precipitation,air temperature and humidity.Keywords: DHF, incidence, descriptive, spatial